Veterinary Epidemiology Principles and Methods - Martin, Wayne S.; Meek, Alan H.; Willebtrg, Preben (Open textbook library., 1987)
The purpose of this textbook is to provide an introductory, yet comprehensive, source of information on epidemiology for veterinary students, researchers, and practitioners. There has not been a textbook that presents analytic epidemiology as a science, basic to veterinary medicine's efforts in health management (herd health) as well as in clinical medicine.